Improvement of DLA sealing machine monitoring process: mechanical design and prototyping of automatic alert system - Abd Rahman, Ramhuzaini; Mohd Rizal, Muhammad Hariz (Research Progress in Mechanical and Manufacturing Engineering, 2023)
In recent times, automation has begun to take over production within the manufacturing industry as it serves to be cost and time efficient. Automated systems that are implemented within the industry are also reliable as they are programmed to work as intended. However, inputs from humans are still required as not all systems have fully transitioned into automated processes. Hence, errors made by humans may still occur from time to time as manual labour is still required within the industry. At TDK Electronics, a problem that has plagued the company during the production of their Surge Arresters, is when their operators mistakenly insert the wrong gas tank to the outlet port of the DLA Sealing Machine after a specified order has been acknowledged by the control panel. This in turn creates faulty products as there is no way of knowing that the gas composition within the surge arrester is incorrect up until the products go through their quality assurance process. Therefore, the aim of this project is to provide a solution for the gas tank exchange problem during the operation of the DLA Sealing Machine. This project presents a case study on the development of a fool-proof gas tank exchange system which requires a step-by-step verification process in order to avoid potential errors with the integration of a barcode system while still adhering to the existing constraints of the DLA Sealing Machine. The mechanism is designed based on the specific dimensions of the existing gas cabinet of the DLA Sealing Machine and the current gas delivery system that is in place. In order to achieve its intended purposes, the new mechanism must be able to eliminate potential errors during the gas exchange process through the incorporation of a verification system that recognizes the gas tanks and its contents as well as alert the operator if any mistakes are made during the exchange process. After the design phase is completed, a simulation that utilizes SolidWorks is conducted on the gas tank exchange mechanism in order to obtain several values from multiple analyses to evaluate the choice of structure, materials and design. The mechanism must be able to withstand 1500mbar of pressure for it to deliver the gas fluids from the gas tanks to the DLA Sealing Machine. It must also be able to withstand industrial use as the machine will be used extensively in the production line to manufacture the surge arresters. A prototype is also developed in order to evaluate the effectiveness of the verification and alert system that was put in place to notify the operator of a potential mistake. The appropriate recommendation is that the new mechanism should be able to meet all the requirements in order for it to be compatible with the current existing system that has been operational since the 1990s.